Cassava Cracker Competitive Advantage Through Product Innovation Quality and Digital Marketing: Keunggulan Kompetitif Kerupuk Singkong Melalui Inovasi Produk, Kualitas, dan Pemasaran Digital - Ramadhani, Cindy; Widayanti, Sri; Rizkiyah, Noor (Indonesian Journal of Innovation Studies, 2026)
General Background The snack food industry faces increasing competition, requiring firms to adopt strategic approaches to maintain competitiveness and sales performance. Specific Background A cassava cracker enterprise experienced a decline in sales volume, indicating challenges in sustaining its market position despite stable raw material supply and product availability. Knowledge Gap Previous studies primarily examine direct relationships between product innovation, product quality, and competitive advantage, with limited attention to digital marketing as a mediating mechanism, particularly in local cassava-based agroindustry contexts. Aims This study analyzes the direct and indirect relationships of product innovation and product quality on competitive advantage through digital marketing as a mediating variable. Results Using a quantitative descriptive method with 96 respondents and SEM-PLS analysis, the findings reveal that product innovation and product quality significantly and positively affect competitive advantage, both directly and indirectly through digital marketing, with digital marketing functioning as a partial mediator. Novelty The study introduces digital marketing as an intervening variable linking innovation and quality to competitive advantage within a localized cassava cracker enterprise context. Implications Strengthening product innovation and maintaining consistent product quality, supported by optimized digital marketing strategies, are essential to expand market reach and reinforce competitive positioning in the snack food industry. Highlights: Innovation and quality significantly strengthen firm competitiveness directly and indirectly. Digital channels function as a partial mediator linking internal capabilities to market positioning. Optimization of online promotion remains limited despite positive statistical relationships. Keywords: Digital Marketing, Product Innovation, Product Quality, Competitive Advantage, Cassava Crackers.